Evaluasi Tata Kelola Repository Perpustakaan UIN SUSKA Menggunakan COBIT 2019 - Rahmat Al Ghani; Salsa Winanda; Winda Elvira; Ghaitsa Dania Azzahra; Megawati Megawati (Pusat Riset dan Inovasi Nasional, 2024)
The development of information technology is very influential on the business world and organizations so that IT governance is needed. This information technology is expected to be useful for stakeholders in making decisions. COBIT 2019 is an IT governance framework that meets the standards in implementing IT governance. The library at UIN Suska Riau has implemented information technology in storing and managing student final assignments or what is known as the UIN SUSKA RIAU Repository system. In conducting a business evaluation, the implementation of the Repository system needs to be maintained, monitored and evaluated for IT governance to determine the process and management of IT usage. After the analysis, it can be seen that the results of the evaluation using the EDM 01, EDM 02 and EDM 03 domains, show that IT governance in the library is at level 3 - established. With some notes that must be analyzed in the EDM 01 domain there is still a lack of communication in IT management, in the EDM 02 domain the application of IT values is not optimal, and what needs to be considered in EDM 03 is the lack of awareness of IT risks.